Repentance in the Quran, Hadith, and Ibn Qudāma's Kitāb al-Tawwābīn - Reynolds, Gabriel Said 1973-; Moghadam, Amir (2021)
The Quran makes repentance an important element of piety and exhorts believers to repent of their sins. Numerous hadith also emphasize its importance, along with God's merciful forgiveness of the repentant sinner. In his K. al-Tawwābīn, the Hanbali scholar Ibn Qudāma al-Maqdisī (d. 620/1223) draws on a wide range of akhbār (always adorned with an isnād) to present examples of repentance of angels, prophets, Companions of Muḥammad, pious mystics, and others, including non-Muslims. Ibn Qudāma's treatise stands out for his frequent citation of accounts (often on the authority of Wahb b. Munabbih) maligned by other scholars as isrā'īliyyāt. In addition, his willingness to highlight the sins of prophets and the Prophet's Companions, while in line with other Hanbalis, challenges common notions of prophetic impeccability and the ethical qualities of the ṣaḥāba. In this article we argue that Ibn Qudāma is willing to challenge these notions because of his vision for the construction of the pious self. He sees human initiative in overcoming the self's natural inclination to sinfulness as a necessary step toward spiritual excellence. In this regard his spiritual vision is shaped by certain Sufi notions. While divine grace still plays a role in the working of repentance, it does not eliminate the need for human initiative. This led Ibn Qudāma to construct a mythical past in which many of the great spiritual figures were involved with a spiritual struggle with their own immoral or impious (or egotistical) instincts.